IRONY AND NOSTALGY. ON MICHAŁ WITKOWSKI'S LITERARY OUTPUT - Czyżak, Agnieszka (Porównania, 2013)
The article is an attempt at sketching the main problems ofMichał Wikowski’s prose. In his novels, the author often returned to the history of People’s Republic of Poland (PRL), as a country governed in 1944–1989 by the Communist authorities, dependent on the USSR. He analysed the experiences of the past in his own way. His narratives, as well as those of other members of the youngest generation of writers, confirmed the common belief that the past should be described in a different manner, because PRL still seems to be an incomplete object of common or even national discourse. Differences of Witkowski’s vision of the last decades result also, or possibly to a larger extent, from his method of using irony and nostalgia – both separately and in a particular conjuction. The success of Witkowski’s attempts depends on the critical awareness of ideological and especially social assumptions, as well as on the ability to identify the crucial questions, i.e. the mental stances and their material conditions, whose common and totalising character strongly influenced (consciously or, more often, subconsciously) choices or decisions of the people living then and there.